Clean the Ni-Rich Cathode Material Surface With Boric Acid to Improve Its Storage Performance - Su, Yuefeng; Chen, Gang; Chen, Lai; Li, Linwei; Li, Cong; Ding, Rui; Liu, Jiahui; Lv, Zhao; Lu, Yun; Bao, Liying; Tan, Guoqiang; Chen, Shi; et al. (Frontiers in Chemistry, 2020)
The existence of residual lithium compounds on the surface of layered Ni-rich materials will deteriorate the electrochemical properties and cause safety problem. This work presents an effective surface washing method to remove the residual lithium compounds from LiNi0.90Co0.06Mn0.04O2 material surface, via ethyl alcohol solution that contains low concentration of boric acid. It's a lowcost process since the filter liquor can be recycled. The optimal parameters including washing time, boric acid concentration, and solid-liquid ratio were systematically studied. It has been determined by powder pH and FT-IR results that the amount of residual lithium compounds was reduced effectively and the storage performance was significantly enhanced for the washed samples. The150th capacity retentions after storing had increased from 68.39% of pristine material to 85.46% ~ 94.84% of the washed materials. The performance enhancements should be ascribed to the surface washing process, which removed not only the residual lithium compounds, but also the loose primary particles effectively.